Pengaruh Motivasi Belanja Hedonis, Kualitas Website Dan Keragaman Produk Terhadap Pembelian Impulsif Konsumen Miniso Pada Website Shopee Di Surabaya Selatan - Maharani, Tyara Kurnia; Agustin, Ni Ketut Yulia; Aditya, Dana (PRAGMATIS, 2023)
The purpose of this research was to know the hedonic shopping motivation, website quality and product diversity affect the impulse buying of miniso consumers on the shopee site in South Surabaya. The population in this study is Surabaya residents who have shopped at Miniso through the Shopee website. The sampling technique used in this study is non-probability sampling using purposive sampling and the research sample obtained is 100 respondents. Data collection techniques using google form. Before testing the hypothesis, test is performed the reliability and validity tests are performed. The result is that all variables are valid and reliable. The results of the t test show each variable with a significance less than 0.05. Thus, "hedonic shopping motivation, website quality, and product assortment have a significant effect on minisio consumer impulse purchases on the shopee website in South Surabaya" can be proven true.